A Rule-Based System for Automatic De-identification of Medical Narrative Texts - Jaćimović, Jelena; Krstev, Cvetana; Jelovac, Drago (Informatica, 2015)
This paper presents an automatic de-identification system for Serbian, based on the adaptation of the existing rule-based named entity recognition system. Built on a finite-state methodology and lexical resources, the system is designed to detect and replace all the explicit personal protected health information present in the medical narrative texts, while still preserving all the relevant medical concepts. The results of a preliminary evaluation demonstrate the usefulness of this method both in preserving patient privacy and the de-identified document interoperability.